ATM Internetworking with ATM - Black, Uyless D. (Prentice Hall series in advanced communications technologies., 1998)
This volume will focus on how to connect ATM networks to a variety of other networks. It will start out with a discussion of the various network interfaces (Data Exchange Interface, InterCarrier Interface, Frame Relay User Network Interface (FUNI). Special focus on Frame Relay and TCP/IP WANs. The book also deals with the issue of Lan emulation and how ATM is employed as a hub in a LAN to support the connections of devices and other LANS. This will be part of a slipcase containing all three ATM volumes from Black.